The preferred story to be told: Adaptation of the figure of the Cid in a didactic-moral text of the 15th century - Lecina Nogués, Laura (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Historical and biblical figures have often been used as a didactic and moral resource, becoming models for a significant part of society. In this process of transformation, an important ideological component, which selects which aspects of the life of these characters can or cannot be told and how this should be done, appears. This study aims to analyse how these reference figures are adapted in the didactic-moral texts of the 15th century, taking as an example the change that the figure of the Cid undergoes in Diego Rodríguez de Almela’s book Valerio de las historias escolásticas y de España.